2004
DOI: 10.1007/bf03325067
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of personality disorders in women with chronic eating disorders

Abstract: The aim of this study was to describe patterns of personality disorders (PDs) in women with chronic eating disorders (EDs). An index group of nineteen women who have had EDs for an average of 8.5 years was compared with a control group of same-aged women from the general population. At the time of the study the index group received treatment at a tertiary treatment center in Stockholm. The PDs were assessed using the DSM-IV part of the DSM-IV and ICD-10 Personality Questionnaire (DIP-Q). In the index group, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…We found the prevalence of definite PD diagnoses in ED patients was lower in this study (21%) compared to other studies (27-95%) [5,6,12,14,17,24,25]. Including a probable PD diagnosis, the overall prevalence was still only 37%.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…We found the prevalence of definite PD diagnoses in ED patients was lower in this study (21%) compared to other studies (27-95%) [5,6,12,14,17,24,25]. Including a probable PD diagnosis, the overall prevalence was still only 37%.…”
Section: Discussioncontrasting
confidence: 84%
“…Several different approaches and diagnostic tools have been used to explore this relationship [1]. In general, research has shown that (1) the prevalence of PDs is higher in populations diagnosed with an ED compared to normal controls [2,3,4,5,6] and (2) inpatients show higher rates of PD comorbidity than outpatients [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The patients' had an average of 4 self-reported personality disorders, which is comparable to the results in a study of women with chronic eating disorders, where the median was 3 personality disorders [29], and to the results in a study of personality disorders in former child psychiatric patients, where the average was 1.7 personality disorders [28].…”
Section: Discussionsupporting
confidence: 80%
“…Personality disorders were screened for with the DSM-IV and ICD-10 Personality Questionnaire (DIP-Q) [28,29]. This instrument is a self-assessment scale.…”
Section: Dip-qmentioning
confidence: 99%
“…Elevated serotonin reuptake in a clinical sample was related to higher perfectionism levels and lower rates of childhood sexual abuse, whereas reduced serotonin reuptake was related to higher rates of childhood sexual abuse and borderline PD [41]. These findings, as well as the aforementioned multivariate aetiological and maintenance models, suggest that, although it is fruitful to consider specific personality traits and disorders alone [42][43][44][45][46][47][48][49][50][51], the consideration of interrelations between personality and bio-psychosocial factors is vital for elucidating the complex and multifactorial pathogenesis of EWDs.…”
Section: Multi-factor Nature Of Eating and Weight Disorder And Personmentioning
confidence: 79%